Exertional Dyspnea as the Main Symptom in an Adolescent Athlete With Coronary Artery Anomaly – A Case Report - Sareban, Mahdi; Hergan, Klaus; Covi, Peter; Niebauer, Josef (Frontiers in Cardiovascular Medicine, 2022)
Coronary artery anomalies (CAA) are associated with sudden cardiac death (SCD) and the majority of these events occur during exercise. Depending on the anatomic features and severity, CAA can provoke stress and/or exercise induced clinical symptoms of myocardial ischemia like arrhythmias, syncope and chest pain. Here we present a case of a female adolescent athlete with a high-risk CAA variant and an unusual clinical presentation, which delayed diagnosis two years after first symptoms were reported. After successful surgical management of the anomalous artery, the patient had an inconspicuous follow-up examinations and was thus determined eligible for competitive sports.